Analysis of Foundation Testing Methods on The Aria Apartemen Batam Construction Project - Rizqi Azmi Arif; Pamadi, Mulia (Journal of Civil Engineering and Planning (JCEP), 2024)
The Aria Apartment project is the construction of a modern apartment complex that requires a strong and safe pile foundation. To ensure the quality and strength of the piles, a PDA Test (Pile Driving Analyzer Test) is carried out. PDA Test is a non-destructive method used to measure the performance and integrity of piles by utilizing vibration waves produced during driving. In this project, the PDA Test was carried out to test the pile bearing capacity against dynamic loads, check the structural integrity of the pile, and ensure that the pile installation complies with the design specifications. This test provides data regarding ultimate compressive strength, energy transfer efficiency, and the possibility of defects or damage to the pile.The PDA Test results show that the piles used in the "The Aria Apartment" project have adequate strength and integrity to support the planned building structure. Thus, the PDA Test is an important part of ensuring the quality and safety of the foundation on this project, as well as providing additional confidence for stakeholders regarding the reliability of the construction.